2019
DOI: 10.1002/anie.201914637
|View full text |Cite
|
Sign up to set email alerts
|

On the Products of Cholesterol Autoxidation in Phospholipid Bilayers and the Formation of Secosterols Derived Therefrom

Abstract: In homogenous solution, cholesterol autoxidation leads to am ixture of epimers of 5 primary products,whose concentrations vary in the presence/absence of antioxidants,such as vitamin E. Tw oo ft he products (5a-OOH and 6b-OOH) undergo Hockf ragmentation to yield electrophilic secosterols implicated in disease.H erein, we show that the product distribution is similar in phospholipid bilayers,i nt hat the 7-OOHs are the major products,but the presence/absence of vitamin Ehas no effect on the distribution. Choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Recent studies showed that C7α-OOH undergoes Hock fragmentation readily, while C7β-OOH is unreactive [40]. This rearrangement does not follow the typical Hock mechanism shown in Figure 7A; instead, an intermediate epoxy carbocation is formed, followed by water entrapment or fragmentation, to give an allylic epoxide that should be highly electrophilic.…”
Section: Cholesterol-derived Electrophilesmentioning
confidence: 97%
See 4 more Smart Citations
“…Recent studies showed that C7α-OOH undergoes Hock fragmentation readily, while C7β-OOH is unreactive [40]. This rearrangement does not follow the typical Hock mechanism shown in Figure 7A; instead, an intermediate epoxy carbocation is formed, followed by water entrapment or fragmentation, to give an allylic epoxide that should be highly electrophilic.…”
Section: Cholesterol-derived Electrophilesmentioning
confidence: 97%
“…The autoxidation of cholesterol incorporated into phosphatidylcholine liposomes gives the same set of products that are found in solution, but the dynamics of reactions in membrane-like vesicles have a significant effect on the product profiles observed when compared to the product distributions found in isotropic solutions. One notable feature of cholesterol autoxidation in phosphatidylcholine liposome is that no evidence of C5α-OOH formation was found when α-tocopherol or PMC was incorporated into the vesicles [40]. This can be understood when consideration is given to the fact that α-tocopherol is a much poorer H-atom donor in phospholipid bilayers (k inh = 4.7 × 10 3 M −1 s −1 ) compared to organic solutions (k inh = 3.6 × 10 6 M −1 s −1 ) due to phenolic hydrogen bonding with the polar headgroup of the phospholipid (see Figure 5A) [87].…”
Section: Cholesterol Autoxidationmentioning
confidence: 99%
See 3 more Smart Citations